(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تناولت هذه الدراسة تحديد تراكيز بعض العناصر المعدنية الثقيلة (Pb,Zn,Ni) في مياه الصرف الصحي المعالجة في ريف مدينة اللاذقية الناتجة عن ثلاث محطات معالجة متوزعة في كل من (حبيت، الحارة، مرج معيربان) خلال عام 2011. اعتمدت هذه الدراسة على مطيافية الامتصاص الذري (AAS) في تحديد العناصر المذكورة أعلاه. أظهرت الدراسة ارتفاع تراكيز عنصر الزنك في جميع المحطات المدروسة وفي جميع الفصول بالمقارنة مع العنصرين الآخرين حيث وصلت إلى (2.798 mg/L) في حين سجل عنصري النيكل والرصاص تراكيز منخفضة نسبياً (0.243, 0.351) mg/L على التوالي. كما أظهرت الدراسة الإحصائية وجود علاقة ارتباط مرتفعة إلى منخفضة أو سلبية أحياناً أخرى مما يعطي مؤشرات واضحة عن مصادر التلوث. This study deals with identifying some heavy metals (Pb,Zn,Ni) concentration in the recycledsewage in Latakia Countryside which is resulting from three treatment plants distributed over (Hebbeit, Al-Harah, MarjMoairban),2011.This research uses the Electro Thermal Atomization-Atomic Absorption Spectrometry (ETA-AAS) technique in determining of heavy metal elements mentioned above. This research shows a higher concentration of Zn-element (2.798 mg/L) in all treatment plants and in all seasons compared with the concentration of other elements, while Ni and Pb have recorded low concentrations (0.351, 0.243) mg/ℓ, respectively. The statistical study has demonstrated that there is a correlation varying from positive high to positive low, and sometimes to negative highs and lows, this gives clear indications for resources of pollution.